BUDAYA POPULER DI ERA DIGITALISASI (STUDI TERHADAP AKTIVITAS INTERAKSI PARASOSIAL PENGGEMAR JKT48 DI SURABAYA) - Muhammad Abdul Rosmi Alwi (Jurusan Ilmu Komunikasi Universitas Andalas, 2023)
In this article, we will discuss the effect of digitalization on the interaction process between JKT48 and fans. The transition of media from conventional to digital began with the new face of the world and a renewal called digitalization. The resulting influence is felt not only by the industrial sector but also by the communications sector. If communication is usually done face-to-face, then with technological sophistication, people can easily interact with others using only digital devices. This has also affected people's consumption patterns as a result of the ease of access to digital products. Based on this phenomenon, business operators are required to be able to innovate so that they do not go into bankruptcy. One of them can be seen in music industry actors, namely JKT48. The idol group innovated by creating a system called Idols You Can Meet.